2022
DOI: 10.1039/d2nj03253h
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of quinoline-based thiadiazole compounds as potential antileishmanial inhibitors

Abstract: Leishmaniasis is a severe disease caused by protozoan parasites of the genus Leishmania and it is accountable for sizable morbidity and mortality worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Interestingly, Khaldan et al also reported that their compounds exhibited similar interactions with the same protein, with the ligand forming critical interactions with Tyr 198, Ile 199, and Arg 287 of TryR. [39] Alpha-bisabolene interacted with TryR majorly via hydrophobic interactions with residues including Gly 11, Gly 13, Val 34, Asp 35, Val 36, Ala 46, Thr 51, Phe 126, Gly 127, Glu 141, Ala 159, Thr 160, Arg 290, and Ala 293, while a very similar interaction profile was maintained by beta-bisabolene. Interestingly, some of the hit compounds reported by Khaldan et al also shared interactions with Gly 13 and Val 36.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Khaldan et al also reported that their compounds exhibited similar interactions with the same protein, with the ligand forming critical interactions with Tyr 198, Ile 199, and Arg 287 of TryR. [39] Alpha-bisabolene interacted with TryR majorly via hydrophobic interactions with residues including Gly 11, Gly 13, Val 34, Asp 35, Val 36, Ala 46, Thr 51, Phe 126, Gly 127, Glu 141, Ala 159, Thr 160, Arg 290, and Ala 293, while a very similar interaction profile was maintained by beta-bisabolene. Interestingly, some of the hit compounds reported by Khaldan et al also shared interactions with Gly 13 and Val 36.…”
Section: Discussionmentioning
confidence: 99%
“…where, ΔGComplex4pt4pt ${\Delta {G}_{Complex\ }{\rm \ }}$ is the total free energy of the protein–ligand complex, and ΔGprotein4pt ${\Delta {G}_{protein\ }}$ and ΔGligand4pt ${\Delta {G}_{ligand\ }}$ are total free energies of the isolated protein and ligand in solvent, respectively. g_mmpbsa can also estimate the energy contribution per residue to the binding energy [38] . To decompose the binding energy, at first ΔEMM4pt,4ptΔGpolar4pt ${\Delta {E}_{MM\ },\ \Delta {G}_{polar\ }}$ and ΔGnon-polar4pt ${\Delta {G}_{non-polar\ }}$ were separately calculated for each residue and were then summed up to obtain the contribution of each residue to the binding energy.…”
Section: Methodsmentioning
confidence: 99%
“…k is the number of descriptors in the model. A leverage value (h) greater than the threshold (h*) suggests that the compound has a large influence on the model [38] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulation is a technique for examining the movement of atoms and molecules, which offers details on the conformational changes in protein–ligand complexes. 46 The three complexes (most active compound 36 , most suitable candidate D3 , and Defactinib as a reference drug) were used as starting structures to better understand the protein–ligand interactions stability. The CHARMM-GUI solution builder created the input files for the MD calculations using the CHARMM force field parameters for proteins.…”
Section: Methodsmentioning
confidence: 99%